FACTORS ASSOCIATED WITH LOWER BIRTH WEIGHT AMONG INFANTS IN SOUTH KALIMANTAN PROVINCE, INDONESIA - Winarno, Nibras Azeenshia; Pujonarti, Siti Arifah; Triyanti, Triyanti; Irawati, Anies; Perkasa, Al Ilham Ksatria Gagah; Sundjaya, Tonny; Masita, Bertri Maulidya (Journal of Indonesian Specialized Nutrition, 2026)
Background: According to the thrifty phenotype hypothesis, individuals who have a Birth Weight less than 3000 grams are at risk of suffering from metabolic syndrome and type 2 diabetes mellitus in adulthood. The prevalence of Diabetes Mellitus and metabolic syndrome in Indonesia and South Kalimantan is increasing. In 2023, the Indonesian Health Survey (Survey Kesehatan Indonesia /SKI) data showed that the percentage of Birth Weight less than 3000 grams in Indonesia reached 35.3% and in South Kalimantan 41.7%. This indicates an increase in the percentage of Birth Weight less than 3000 grams in South Kalimantan when compared to the 2018 Riskesdas data, the percentage of BW less than 3000 grams in South Kalimantan was 37.5%. This is a quantitative study using a cross-sectional research design and using secondary data from the SKI 2023. Data were analyzed univariately and bivariately with complex samples and chi square tests. The results of the study found a significant association between Birth Weight and Chronic Energy Deficiency (p-value = 0.001) where mothers with a history of Chronic Energy Deficiency had a 5 times higher risk. Conclusion: History of Chronic Energy Deficiency among mothers is an important determinant of infants’ Birth Weight in South Kalimantan. Further, these findings might contribute to the prevention strategy of Non-Communicable Diseases in South Kalimantan.